(untitled) (Al-Academy, 2021)
The tagged research is concerned with observation and investigating the concepts of consistency and harmony in contemporary Iraqi painting (selected models) in order to reveal the mechanisms and rules of these two concepts in the artistic field and their mechanisms of operation. How reflected tools Consistency and harmony in contemporary Iraqi painting? What is consistency and what are its mechanisms and principles? Is consistency a unit product quality? Are there similarities between consistency and harmony? What is harmony and its principles and rules? As for the second chapter, it included two topics that dealt with the first topic - consistency and harmony between concept and significance, while the second topic meant - historical reading in contemporary Iraqi painting (roots and origins), and the third chapter included research procedures, as the framework of the research community was defined, and sample models were chosen The amount (5) is five technical works, and the treatments of the Research Department were reviewed and the samples analyzed, while the fourth chapter concerned the results of the research, their discussion and conclusions.